Mental Resilience of Indonesian Career Women In Responding To Marriage-Related Social Pressure - Atikah Rahmah Nasution; Rizki Wulandari (International Journal of Education, Language, and Social Science, 2026)
This study examines the mental resilience of Indonesian career women in responding to marriage-related social pressure, particularly the recurring question “When will you get married?”. Previous studies have discussed social stigma and psychological pressure toward unmarried women; however, limited studies specifically analyze this phenomenon through the perspective of resilience theory among career women in Indonesia. This study employed a qualitative literature review method using journal articles indexed in Google Scholar, SINTA, and Scopus published between 2018 and 2026. Data were collected using keywords related to career women, marriage pressure, mental resilience, and social stigma. A total of 47 relevant articles were analyzed through thematic analysis techniques. The findings reveal that marriage-related social pressure contributes to anxiety, stress, loneliness, decreased psychological well-being, and reduced interest in marriage among career women. Furthermore, mental resilience plays a significant role in helping women manage emotional pressure, maintain self-confidence, and develop adaptive coping strategies. This study contributes to the development of resilience psychology discourse, particularly in understanding the relationship between gender expectations, social pressure, and mental well-being among career women in Indonesia.